Early Childhood Education in Thailand (Training and Practice : Journal of Educational Sciences, 2014)
The relationship between the University of West Hungary, Benedek Elek Faculty of Pedagogy and the Naresuan University, Faculty of Education, is relatively fresh. The Thai partner has already been to Sopron, in the course of their visit they have settled the fundamentals of a future cooperation. This study and teaching visit aimed at the expansion of our future research cooperation as they were amazed by the early childhood education training programme elaborated by the University of West Hungary, Benedek Elek Faculty of Pedagogy. This study visit was a joint project of Mr Katona, László PhD and Mr Varga, László PhD who planned to represent their university together in Thailand. Mr László Katona was involved with scientific education (natural sciences) focusing on how children see the world through natural sciences while Mr László Varga concentrated on the latest trends in early childhood development.We introduced our expertise to Thai students and to the staff at the same time, which we believe was very fruitful to our scientific and educational as well as training spectra. Besides lecturing we were able to design a large scale international comparative educational research into the characteristics of early childhood in Thailand and Hungary. This visit also aimed at the further elaboration of the possible future student and teacher mobility programmes. The results of this study visit are going to be disseminated in various national and inernational scientific journals and through informative workshops both in Thailand and in Hungary.